PERAN MEDIASI KEPUASAN KONSUMEN PADA DETERMINAN KEPUTUSAN PEMBELIAN ULANG WEDANG UWUH HALAL - Dwi Karti Handayani; Lukia Zuraida (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
A brand trust that has been highly expected by consumers indicates the brand image of the product is also high, thus moving consumers to make a purchase of a product. The research method used in this study is quantitative with a cross sectional design. The sampling technique in this study used convenience side techniques with 100 respondents. The data collection method used a closed questionnaire and the analysis technique used is PLS. The results showed that product quality has a positive effect on customer satisfaction and repurchase decision. Brand trust has a positive effects on customer satisfaction but has no effect on repurchase decision. Consumer satisfaction has a positive effect on repurchase decision. Consumer satisfaction mediates product quality and brand trust on the repurchases decision of wedang uwuh halal.